YUDAS ISKARIOT DALAM PERSPEKTIF TEOLOGIS: ANTARA KEHENDAK BEBAS DAN DETERMINISME ILAHI DALAM NARASI PENEBUSAN - Paul Stefan Maabuat (PT. Giat Konseling Nusantara, 2025)
This study explores the role of Judas Iscariot from a theological perspective,focusing on the dialectic between free will and divine determinism within the narrative of Christ’s redemption. Using a compatibilist approach, the research highlights how Judas’s act of betrayal is both a free moral choice and an integral part of God’s providential plan. The findings reveal that the tension between human freedom and divine sovereignty is a theological mystery to be embraced, with significant ethical and spiritual implications regarding sin, responsibility, and grace. The study concludes that Judas’s role extends beyond being a mere betrayer, serving as a symbol of the existential struggle between evil and salvation in contemporary Christian faith.